Methods of da’wah and social networks in dealing with liberalism and extremism - Ahmad Munawar Ismail,; Wan Kamal Mujani,; Ahmad Aiman Zuhaily A.M, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Da’wah is the responsibility of all Muslims at all levels. Besides spreading the teachings of Islam, da’wah is essential to raise awareness to all societies that the teaching of Islam has been disseminated are true, pure and from a genuine source. This article deals with the method of da’wah and social networks in dealing with liberalism and extremism. It discusses how far da’wah movements and social networks can be used effectively to meet the challenges of liberal and extreme ideology in Malaysia. By using the qualitative, historical, and content analysis, this article is part of the research findings on collective and multi-disciplinary approaches in combatting extremism ideology and activities in Malaysia. The research findings show that these two ideologies (liberalism and extremism) are transmitted through social networking technologies including Facebook, WhatsApp and Twitter. This media technology not only facilitates communication, but, despite all these facilities they are very dangerous and has social implications. A free understanding, an extreme, a radicalism and in similar with it are widely disseminated through the sophistication of this technology. In this case, the method of da’wah should be updated from time to time, up to date and utilize of all available technologies. In addition, in order to spread the genuine Islamic teachings and eradicate the wrong doctrine, the greatest challenge is to ensure that all information’s to be disseminated are true and genuine derived from the principles of Sunnah.